Knowledge, culture and the curriculum in Britain, 1944 to the present (UCL Press, 2022)
The school curriculum is a vital battlefield on which versions of the 'good society' are fought over. For much of the past five decades, the educational left has been losing that battle. Optimistic calls for a curriculum to support a 'common culture' fragmented in the face of economic, social and cultural changes. This article charts debates about curriculum and culture, focusing on the work of the sociologist of education Michael Young, who spent his academic life at the IOE (Institute of Education), UCL's Faculty of Education and Society (University College London, UK). It surveys the educational arguments of the New Left in the 1960s, the turn towards knowledge and control and neo-Marxism in the 1970s, the failed modernisations of the 1990s and the influence of postmodern culture on curriculum and school subjects. Finally, it assesses recent moves to reassert the importance of knowledge over skills and processes. The crisis in curriculum is reflective of wider crises in British society, and, it is suggested, Young offers a guide to what comes next.